Anaesthesia, Pain, Intensive Care and Emergency Medicine — A.P.I.C.E. Proceedings of the 13th Postgraduate Course in Critical Care Medicine Trieste, Italy — November 18–21, 1998 - Gullo, Antonino (Springer Milan, 1999)
The management of the critically ill patients has been in the past few years a discipline at the forefront of development which continues to make progress with the support of basic and clinical research. This work is a collection of material that deals with the management of critically ill patients, published on the occasion of the 13th APICE congress in November 1998, which celebrated 40 years of Critical Care Medicine
Keywords: Anesthesiology; Intensive / Critical Care Medicine; Critical care medicine; Anästhesie; Notfalltherapie; Schmerztherapie; Intensivtherapie; Konferenzschrift -- 1998 -- Triest